Scoping Review Peran Konteks Sosial dalam Pemberian ASI Ekslusif - Meher, Cashtri; Zaluchu, Fotarisman (Inovasi, 2024)
Exclusive breastfeeding for the first six months of a baby's life has been proven to provide significant benefits, both in terms of health and developmental outcomes. However, in many countries, including Indonesia, the coverage of exclusive breastfeeding remains very low, contributing to high rates of malnutrition, including stunting. This scoping review was conducted to identify and analyze the social factors influencing the practice of exclusive breastfeeding, with the aim of informing more effective intervention strategies. The study employed a scoping review methodology, involving a comprehensive literature search across three major databases: PubMed, Scopus, and Google Scholar, covering publications from 2014 to 2024. Of the 401 articles identified, 7 were selected for analysis following a rigorous selection process. The review findings indicate that support from husbands, extended family, and the broader social environment are key factors in the success of exclusive breastfeeding. Identified barriers include a lack of family support, the influence of local cultural beliefs, misinformation about breastfeeding, and misconceptions regarding infant needs. These factors significantly affect mothers' decisions to practice exclusive breastfeeding. Furthermore, the role of healthcare professionals in providing accurate education to mothers and families is crucial in improving exclusive breastfeeding rates. In conclusion, to enhance the success of exclusive breastfeeding, a comprehensive approach involving the entire family and considering local cultural contexts is required. Policy support, intensive educational campaigns, and improved access to lactation counseling services should be prioritized to achieve higher exclusive breastfeeding rates in Indonesia.